Adaptasi Masyarakat Kawasan Lumpur Lapindo dalam Memenuhi Kebutuhan dan Ketersediaan Air Bersih - Putri, Aurellya Abdillah Wijaya; Sudarti, Sudarti (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2021)
The Lapindo mudflow became one of the disasters that occurred in Sidoarjo Regency. As a result, it is difficult for villages around the Lapindo mud area to get clean water. This study aims to determine the adaptation of the community in meeting the needs and availability of clean water, to find out the decisions made by the government regarding the availability of clean water in the affected areas. This study uses a qualitative descriptive method with interviews and interviews with people in areas affected by the Lapindo mud, especially Gempolsari village residents to find out what the community has done and the decisions that have been made by the government since the Lapindo mudflow. The results of this study indicate that there have been responsive and anticipatory adaptation efforts carried out by Gempolsari village residents but the government has not been able to maximize assistance to affected victims. Efforts are being made to buy clean water, look for sources of clean water and try to get clean water assistance from the government. However, adaptation to the use of appropriate technology to manage water has not been implemented in Gempolsari village. Keywords: Lumpur Lapindo, Clean water, Adaptation of community